Conducta impulsiva en adolescentes testigos de violencia familiar - Negrete Cortés, Agustín (2023)
The aim of this study was to assess the impulsive behavior under the model of matching law in a group of teenagers, witnesses of family violence, using a paradigm of choice in where they manipulated the four dimensions of the reinforcer: quality, immediacy, effort and reinforcement program and to compare their performance with a group of teenagers who are not witnesses of family violence. The age of participants was between 14 and 17 years old, they all were students of high school in Mexico City, which 28 were men and 17 women. Each participant completed seven sessions: a baseline assessment, five assessments of impulsive behavior and replication. The results indicate that the group of adolescents, witnesses of family violence, do not differ significantly from the comparison group in the number of impulsive choices, however, differences do occur when the quality competes against the effort. There is a tendency of adolescents witness of family violence to choose a lower effort even if it means getting a low-quality reinforcer. The results are discussed in terms of relevance to assess the construct of impulsivity from a paradigm of choice in a nonclinical population with specific characteristics.